Influencing factors on customer satisfaction towards American brands in the food and beverage industry in Malaysia / Nur Atiqah Rochin Demong, Abdul Kadir Othman and Salmi Bawasa. - Rochin Demong, Nur Atiqah; Otman, Abdul Kadir; Bawasa, Salmi (Universiti Teknologi MARA Cawangan Selangor, 2016)
Customer satisfaction is the ultimate aim to food and beverage F&B industry as it ascertains that satisfied customers will stay loyal and reduce the amount of complaints towards their brand of choice. The main purpose of the research is to understand the influencing factors on customer satisfaction towards American brand in F&B industry in Malaysia. Convenience sampling method was used involving the respondents that consist of customers and shoppers within five mega malls in Kuala Lumpur to represent the total population of the study. The researcher used a multiple regression analysis to analyze 384 data from customers. The results indicate a positive and significant influence of all influencing factors (perceived quality, perceived value and Customer Expectation) on customer satisfaction. Customer expectation is seen to be the factor that was highly influential towards satisfaction, followed by perceived quality and perceived value. The implications of the study are discussed in the paper.